The Control Method for Wavelength-Based CCT of Natural Light Using Warm/Cool White LED - Yang-Soo Kim; Seung-Taek Oh; Jae-Hyun Lim (Proceedings of Engineering and Technology Innovation, 2023)
Reproducing circadian patterns of natural light through lighting requires technology that can control correlated color temperature (CCT) and short wavelength ratio (SWR) simultaneously. This study proposes a method for controlling wavelength-based CCT of natural light using LED light sources. First, the spectral power distribution (SPD) of each channel of the test lighting (two-channel LED lighting with warm white and cool white) is identified through actual measurement. Next, CCT and SWR are calculated based on the additive mixing of SPD using the mixing ratio from the measured SPD. Finally, the regression equations for mixing ratio-CCT and mixing ratio-SWR are derived through regression analysis. These equations are then utilized to implement a wavelength-based CCT control algorithm. For performance and evaluation purposes, natural light reproduction experiments were conducted, achieving a mean error of 94.5K for CCT and 1.5% for SWR.